A study on the applicability and usability of Graphology as management tool for assessing employees’ competencies - Ms. Asmita Gargote; Dr. Revati Deshapande (The Bioscan, 2025)
Graphology is a powerful tool for understanding a person's overall personality, abilities, growth potential, integrity, and stress levels. This scientific method is based on analysing strokes and their combinations, which have significant interpretations. Research has demonstrated the validity of graphology through comparative studies with other psychometric tests, showing its effectiveness in assessing an employee's competencies. The role of graphology in human resources is examined in this paper. While there are numerous methods to gauge a person's skills, there is a lack of a scientifically foolproof method to assess their personality. An individual with suitable skills but unsuitable personality traits or high-stress levels may not be the right fit for a given task or role. Handwriting, being a unique physical process, reflects the writer's state of mind as the brain signals control the fingers during writing. This study can be used to analyse specific characteristic features of an individual, and this paper discusses various applications of graphology as a management tool.